Instalación inmediata de prótesis provisionales en la reapertura de implantes - Chávez, Alejandro Munõz [UNESP]; Mollo Junior, Francisco de Assis [UNESP]; Corrêa, Cássia Belloto [UNESP]; Muñoz-Chávez, Oscar Fernando [UNESP] (My University, 2007)
The study of techniques to reach aesthetics in the anterior region when using osseointegrated implants is of great importance. A literature review was made to compare effivciency and suitability of immediate provisionalization in re-opening of osseointegrated implants with respect to the set time (use of standardized cicatrizants and emergency profile cicatrizants). Immediate provisional denture in the phase of re-opening makes the restoration of the gingival contourn quicker when compared to the use of cicatrizants without intermediate phases required. © 2008 1995, Editorial Ciencias médicas.
Immediate instalation of provisional protheses in implant reopening
Keywords: Anterior aestherics; Emergency profile; Provisional denture